2021
DOI: 10.1021/acsaem.1c02456
|View full text |Cite
|
Sign up to set email alerts
|

Mo2C-MXene/CdS Heterostructures as Visible-Light Photocatalysts with an Ultrahigh Hydrogen Production Rate

Abstract: Here, we report a visible-light photocatalyst (Mo 2 C-MXene/CdS) with H 2 production rate higher than that of state-ofthe-art catalysts based on noble metals or other MXenes. The photocatalyst was constructed from Mo 2 C MXene, Cd(NO 3 ) 2 • 4H 2 O, and thiourea with ethylenediamine, which has an acanthosphere structure with Mo 2 C two-dimensional (2D) sheets covered by wurtzite CdS nanocrystals. From theoretical calculation, Mo sites in the Mo 2 C-MXene/CdS(110) heterostructure provide an efficient reaction s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…The number of formed heterostructures between CdS and MoO 2 @Mo 2 C-MXene increases with the loading of MoO 2 @Mo 2 C-MXene, which is beneficial to the enhancement of photocatalytic activity. In particular, the optimal sample of CMM5 exhibits the best H 2 production rate of 22,672 μmol/(g•h), which is ~21% higher than that of CdS/Mo 2 C [43]. The reduction of photocatalytic activity with the further increase of MoO 2 @Mo 2 C-MXene is probably because excessive MoO 2 @Mo 2 C-MXene can cover the active sites of the catalysts [28,56].…”
Section: Photocatalytic Propertiesmentioning
confidence: 96%
See 1 more Smart Citation
“…The number of formed heterostructures between CdS and MoO 2 @Mo 2 C-MXene increases with the loading of MoO 2 @Mo 2 C-MXene, which is beneficial to the enhancement of photocatalytic activity. In particular, the optimal sample of CMM5 exhibits the best H 2 production rate of 22,672 μmol/(g•h), which is ~21% higher than that of CdS/Mo 2 C [43]. The reduction of photocatalytic activity with the further increase of MoO 2 @Mo 2 C-MXene is probably because excessive MoO 2 @Mo 2 C-MXene can cover the active sites of the catalysts [28,56].…”
Section: Photocatalytic Propertiesmentioning
confidence: 96%
“…Mo 2 C MXene is another MXene prepared by etching Mo 2 Ga 2 C [38][39][40][41][42]. In the previous work [43], we found that Mo 2 C-MXene/CdS heterostructure exhibited an ultra-high H 2 production rate of 17,964 μmol/(g•h).…”
Section: Introduction mentioning
confidence: 99%
“…The M@T/CIS photocatalyst exhibited a high H 2 evolution rate of 356.27 μmol·g −1 ·h −1 , which was about 69.5 and 636.2 times higher than that of the Ti 3 C 2 MXene@TiO 2 (M@T) and CIS sample, respectively. Jin et al [ 119 ] constructed Mo 2 C-MXene/CdS heterostructures as photocatalysts by the hydrothermal method. The experiment of photocatalytic hydrogen production showed that the photocatalyst showed excellent hydrogen production performance compared with the previously reported Ti 3 C 2 MXene catalyst.…”
Section: Applications Of Mxene-based Heterostructuresmentioning
confidence: 99%
“…When using an in situ HF-formed etchant, intercalation proceeds at the etching step due to the presence of Li + , NH 4 + , or K + ions. In the case of the basic intercalant, the MXene phase is further washed to obtain a pH below 8 [171,182,183].…”
Section: Synthesis Of Mxenesmentioning
confidence: 99%
“…Recently, an increasing number of research reports on modified metal carbides from the MXene group to improve catalytic [169,180], conducting [186,187], photocatalytic [167,182], and optical response properties [167,182] have been published. He et al [187] synthesized Ni 1.5 Co 1.5 S 4 @Ti 3 C 2 nanocomposites for high-performance supercapacitors.…”
Section: Modification Of Mxenes With Other Compoundsmentioning
confidence: 99%